Maternal Serum Concentrations of Selenium, Copper, and Zinc during Pregnancy Are Associated with Risk of Spontaneous Preterm Birth: A Case-Control Study from Malawi - Grace Chiudzu; Augustine T. Choko; Alfred Maluwa; Sandra Huber; Jon Odland (Journal of Pregnancy)
Preterm birth is delivery before 37 completed weeks. A study was conducted to evaluate the association of maternal serum concentrations of selenium, copper, and zinc and preterm birth. There were 181 women in this nested case-control study, 90/181 (49.7%) term and 91/181 (50.3%) preterm pregnant women. The overall mean serum concentration of selenium was 77.0, SD 19.4 μg/L; of copper was 2.50, SD 0.52 mg/L; and of zinc was 0.77, SD 0.20 mg/L with reference values of 47-142 μg/L, 0.76-1.59 mg/L, and 0.59-1.11 mg/L, respectively. For preterm birth, mean serum concentration for selenium was 79.7, SD 21.6 μg/L; for copper was 2.61, SD 0.57 mg/L; and for zinc was 0.81, SD 0.20 mg/L compared to that for term births: selenium (74.2; SD 16.5 μg/L; p=0.058), copper (2.39; SD 0.43 mg/L; p=0.004), and zinc (0.73; SD 0.19 mg/L; p=0.006), respectively. In an adjusted analysis, every unit increase in maternal selenium concentrations gave increased odds of being a case OR 1.01 (95% CI: 0.99; 1.03), p=0.234; copper OR 1.62 (95% CI: 0.80; 3.32), p=0.184; zinc OR 6.88 (95% CI: 1.25; 43.67), p=0.032. Results show that there was no deficiency of selenium and zinc and there were high serum concentrations of copper in pregnancy. Preterm birth was associated with higher maternal serum concentrations of copper and zinc.